Pengaruh Tunjangan Kesejahteraan, Disiplin Kerja Terhadap Kinerja Karyawan dan Dampaknya Terhadap Prestasi Kerja PT. Ace Hardware Artha Gading - Elsya Meida Arif; Ari Putera (Fakultas Ekonomi Universitas Borobudur, 2020)
This research is a survey research using a questionnaire as the instrument. The populationin this study is the population that will be the object of research are 110 employees of PT ACEHARDWARE ARTHA GADING. A sample of 86 respondents using purposive sampling method,which is based on criteria users.The data used in this study are primary data collected from the results Respondents'answers based on the questionnaire given, as many as 86 people. Method Data processing usesthe path analysis method with the help of the SPSS version 23.0. Statistical testing using partialsignificance test (T test) and simultaneous significance test (Test F).The results of the study show that the welfare benefits have an effect on Employeeperformance at PT. Ace Hardware Artha Gading, Work Discipline affects Employee performanceat PT. Ace Hardware Artha Gading, influential welfare benefitson Job Performance at PT. AceHardware Artha Gading, influential work discipline on Job Performance at PT. Ace HardwareArtha Gading, influential employee performance on Job Performance at PT. Ace Hardware ArthaGading, Welfare Benefitsindirect effect on work performance through employee performance atPT. AceArtha Gading Hardware, Work Discipline has an indirect effect on Job Performancethrough Employee Performance at PT. Ace Hardware Artha Gading.Keywords: Welfare Benefits, Work Discipline, Employee Performance and Achievements Work